Videojuego para la evaluación y rehabilitación cognitiva de las funciones ejecutivas en niños - Ramírez Galíndez, Natalia (Universidad de San Buenaventura - Cali, 2019)
The main objective of this research is to evaluate the effectiveness of a video game as a tool for rehabilitation or cognitive stimulation. Currently there are some rehabilitation programs where commercial video games are used as tools to perform stimulation processes with very promising results in terms of improving skills such as working memory, attention and perception. Besides this, videogames can have an emotional and motivational component that does not possess rehabilitation or traditional cognitive training. Therefore, the research was carried out through the application of the VISOR video game designed in the Psychology Laboratory of the University of San Buenaventura Cali for the rehabilitation of the Executive Functions. The game was applied to a group of children between the ages of 7 and 11 who were enrolled in the third, fourth and fifth grades of primary school (experimental group). Additionally, the Children's Neuropsychological Evaluation battery was used to compare the results of the first group with those of the control group by means of a pre-test and post-test comparison and thus determine the viability of the tool used for the rehabilitation process